Cisco security professional's guide to secure intrusion detection systems - Burton, James; Dubrawsky, Ida.; Osipov, Vitaly; Baumrucker, C. Tate.; Sweeney, Michael (Rockland, MA : Syngress Pub., 2003)
Cisco Systems, Inc. is the worldwide leader in networking for the Internet, and its Intrusion Detection Systems line of products is making in roads in the IDS market segment, with major upgrades having happened in February of 2003. A comprehensive, up-to-date guide to the hardware and software that comprise the Cisco IDS. This book does more than show network engineers how to set up and manage this line of best selling products ... it walks them step by step through all the objectives of the Cisco Secure Intrusion Detection System course (and corresponding exam) that network engineers must pass on their way to achieving sought-after CCSP certification. * Offers complete coverage of the Cisco Secure Intrusion Detection Systems Exam (CSIDS 9E0-100) for CCSPs.
Installation and Setup; Pervasive Network-based and Host-based protection; Real-Time Intrusion Detection; Response to Unauthorized Activity; Intrusion Alarms; Scalability; Remote Configuration Capability; Attack Database; User-Defined Signatures; Notification actions; Automatic Signature; Web-based embedded device management; IDS Anti-Evasion Techniques.
Includes index.
Keywords: Computer networks -- Security measures; Computer security; Electronic books